INNOVATION IN HIGH-RISE GREEN SPACE IN PANTAI INDAH KAPUK, JAKARTA - Firly Putri Irenewati; Martinus Bambang Susetyarto (Journal of Synergy Landscape, 2025)
In recent years, attention to the desire for architectural development has increased, especially in applying high-rise green spaces. However, questions about the application in designing nature contribute to the desires and challenges. Then, there are rarely seen examples of the application of three-dimensional greening in high-rise buildings in the Pantai Indah Kapuk area, Jakarta. This study aims to explore the application of biophilic principles in designing high-rise green spaces and their impact on environmental quality, then show one example of a high-rise building that applies three-dimensional greening in the Pantai Indah Kapuk area. The method used is the framework of Stephen R. Kellert and 14 Biophilic Design Patterns from Terrapin Bright Green, which have been modified based on Zhong's research related to designing with nature, namely green space in architecture through a biophilic design framework and the desire to assess the application of biophilic principles in two case studies and one example of a building that applies biophilic principles in the Pantai Indah Kapuk area. The study results show that three-dimensional green space inside the building is still minimal because evaporation in plants makes the interior humid. There are some in the case study, but some are related to the function of commercial buildings and the placement that gets a lot of sunlight. Therefore, the application of biophilic in two case studies and one example of a building in the Pantai Indah Kapuk area on the outside of the building, while inside the building still creates natural elements but resembles nature, both in the form of the building mass and the decoration inside the room.